The thinking styles of the university teacher (2019)
This article is related to the ways of thinking of the teacher; his goal was to understand the thinking styles of the university teacher from two out of the five cognitive and behavioral expressions in Sternberg’s thinking styles theory: the function inside the classroom and the level of classroom performance. The epistemological approach was the empirical-inductive, framed in the logic positivism tradition, with the case study as methodolo-gy. A 24-item likert-based scale was applied to 40 teach-ers of the Education career from Universidad Francisco de Miranda (UNEFM) - Venezuela. The results evi-denced a mediational thinking style, based on cognitive and constructivism-based teaching procedures, democratic patterns for classroom organization, as well as a permanent process of reflection that informs teachers about what and how to improve while teaching. These results can help to optimize teaching performance, as well as to design pedagogical training processes more focused and based on mediational pedagogies that lead to better learning.